Дослідження методів та програмних засобів аналізу новинних стрічок в соціальних мережах - Сердюк, О. О. (My University, 2018)
The article is devoted to the methods of text mining, analyzing text and weighting words in a document in order to retrieve words those are more semantically focused. That helps to retrieve information about it main topic, tone and content.
Keywords: methods of text mining